Activating public loan contracts to fund local development, at Eastern Algerian Coastal Municipalities: Centralization, human, and legal difficulties - Lakikza, Yacine; Boulksibat, Mahfoud (The International tax journal, 2025)
Public loan agreements have become a viable but underutilized method of funding local development initiatives in Algeria due to the growing financial strains on local governments. With an emphasis on El Tarf, Annaba, and Skikda, this study investigates the administrative, legal, and human resource obstacles that prevent public loan contracts from being activated among eastern coastal municipalities. The ambiguity of legal frameworks, inadequate administrative capabilities, over-centralization, and the incompetence of elected officials were among the recurring challenges identified by a field study employing structured questionnaires in 24 municipalities. The results highlight how urgently human capital development, regulatory reforms, and a more decentralized governance model are needed to enable municipalities to achieve financial autonomy. In order to maximize the use of public loan mechanisms and support sustainable local development financing, practical recommendations are put forth.